Breathing and heart rate of Arab-speaking students using the Russian language - Liuzina, Kseniya M.; Al-Tawil, Noha; Chumak, Anatoly G. (Experimental Biology and Biotechnology, 2018)
The analysis of the dynamics of changes in speech breathing and heart rate variability, conducted using computer- based methods of investigation, revealed the patterns of activation of the autonomic nervous system in students with native Arabic when mastering a university course in Russian. Six healthy people, citizens of Libya (4 men and 2 women), aged 23 to 32 years were examined. Only certified instruments available at the Department of Human and Animal Physiology: spirometer МАС-1, manufactured by Unitechprom (Belarus), Neurosoft-psychotest, multifunctional computer complex Neuron-Spectrum, manufactured by Neurosoft, Russia were used. The manifestation of speech breathing in students who have a native Arabic language is different when speaking in Russian and Arabic. The patterns of respiration do not correspond to each other, although the main parameters of external respiration differ to a lesser extent with preservation of saturation of peripheral blood of oxygen at normal level. The variability of the heart rhythm increases dramatically when reading or pronouncing phrases in Russian, then when speaking in Arabic. The analyzed parameters of heart rate variability confirm the tension of the mechanisms of vegetative accompaniment of the speech function when learning a new language for yourself.